2020
DOI: 10.1051/matecconf/202033001012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of QW coupling on the binding energy in InGaN/GaN under the effects of the size, the impurity and the internal composition

Abstract: In the present paper, the binding energy of hydrogenic shallow-donor impurity in simple and double coupled quantum wells based on unstrained wurtzite (In,Ga)N/GaN is investigated. Considering the effective-mass and dielectric mismatches between the well and its surrounding matrix, the numerical calculations are performed within the framework of the parabolic band and the single band effective-mass approximations under the finite potential barrier using finite element method (FEM). According to our results, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Finally, we report in Figure 5 the variation of binding energy of an on-center shallow donor impurity versus the side barrier width for diverse values of the coupling barrier width (𝐻) and fixed parameters 𝑥 = 0.1 and 𝑇 = 300 𝐾. The behavior of the ground state binding energy as a function of 𝐿 is similar to that found in our previous work [37] for simple and double rectangular QWs, i.e., the binding energy augments (drops) with decreasing the barrier width for a low (strong) confinement regime. The physical reason is that for strong confinement, the entire wave function is in the barrier, the more the barrier width increases the more the wave function spreads in the barrier which reduces the binding energy.…”
Section: Numerical Results and Discussionsupporting
confidence: 74%
“…Finally, we report in Figure 5 the variation of binding energy of an on-center shallow donor impurity versus the side barrier width for diverse values of the coupling barrier width (𝐻) and fixed parameters 𝑥 = 0.1 and 𝑇 = 300 𝐾. The behavior of the ground state binding energy as a function of 𝐿 is similar to that found in our previous work [37] for simple and double rectangular QWs, i.e., the binding energy augments (drops) with decreasing the barrier width for a low (strong) confinement regime. The physical reason is that for strong confinement, the entire wave function is in the barrier, the more the barrier width increases the more the wave function spreads in the barrier which reduces the binding energy.…”
Section: Numerical Results and Discussionsupporting
confidence: 74%
“…Furthermore, H. Bahramiyan, and coworker, have demonstrated that the binding energy is larger when the impurity locates at the position of maximum probability due to the reason that the stronger Columbic coupling provided that the electronic density of probability has its maximum located exactly at the impurity-position [15]. In the same context, W.Belaid and coworkers have proved that the impact of the impurity's position is more significant in DQW in particularly for the moderate confinement regime [6].…”
Section: Resultsmentioning
confidence: 94%
“…The binding energy of hydrogen-like impurity in nanostructured semiconductors made out with different band-gaps materials under various effects concerning different electronic-states has been reported in many works. H. El Ghazi, and coworkers have investigated the stark effect and pressure-dependent on ground-state donor binding energy in InGaN/GaN square and parabolic QWWs [6] - [7]. The effect of a spatially dependent effective mass on the hydrogenic impurity binding energy in a finite parabolic quantum well has been reported by XH.Qi et al [8].…”
Section: Introductionmentioning
confidence: 98%
“…Minimizing spectral line broadening, influenced by factors like indium composition fluctuations and interface roughness, is essential for applications requiring narrow linewidths. Temperature dependence affects carrier dynamics, and achieving optical gain in InGaN/GaN QWs is crucial for their use in semiconductor lasers [33,34]. Ongoing research actively addresses challenges such as the "green gap" and material degradation, focusing on new designs and manufacturing techniques to enhance the efficiency and reliability of InGaN/GaN QWs in practical optoelectronic devices [35].…”
Section: Introductionmentioning
confidence: 99%